If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2 + -6) = -15m + -3m + -6 Combine like terms: 2 + -6 = -4 3(-4) = -15m + -3m + -6 Multiply 3 * -4 -12 = -15m + -3m + -6 Reorder the terms: -12 = -6 + -15m + -3m Combine like terms: -15m + -3m = -18m -12 = -6 + -18m Solving -12 = -6 + -18m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '18m' to each side of the equation. -12 + 18m = -6 + -18m + 18m Combine like terms: -18m + 18m = 0 -12 + 18m = -6 + 0 -12 + 18m = -6 Add '12' to each side of the equation. -12 + 12 + 18m = -6 + 12 Combine like terms: -12 + 12 = 0 0 + 18m = -6 + 12 18m = -6 + 12 Combine like terms: -6 + 12 = 6 18m = 6 Divide each side by '18'. m = 0.3333333333 Simplifying m = 0.3333333333
| -8(1+5b)=-168 | | -8(1+5b)=168 | | 18/(8-6)x3 | | 2x-x=3630 | | T^2-4T=6 | | -7m+12+5=-15 | | Y^2-44y=0 | | 4y=42-2x | | 92/6 | | 50x(90-x)/900x | | x/4-11 | | ln(x-2)=2lnx-ln(2x-3) | | 4x+15=6x+3 | | y/2=6 | | 7x-38.65=3.35 | | 60+90+2n=180 | | -2(5x+3)=-86 | | v^2=-1 | | (a^2-4a+6)+(-3a+13a+1)=0 | | 4.2z+8.5=214.3 | | p^2=-49 | | 4(8x-42)=88 | | -11=x+23 | | 6x(7x-6)-6=0 | | 5(x-2)=3x+18 | | -6.5a=325 | | 2x-3/1.12=x/5 | | -17=4v+7 | | 3800/395 | | y-(-5)=15y | | 4/7=16x | | 2w=-18 |